2023
DOI: 10.7759/cureus.37271
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Staple Line Reinforcement With Ligation Clips for Hemostasis in Laparoscopic Sleeve Gastrectomy

Abstract: Introduction: In Pakistan and worldwide, there is a lack of literature on the role of ligation clips in controlling hemostasis in laparoscopic sleeve gastrectomy. ligation clips are being used to secure hemostasis and act as staple line reinforcement to prevent intra-operative and postoperative bleeding. Data can be utilized to reflect the role of staple line reinforcement with ligation clips so as to guide surgeons about its safety and efficacy.Methodology: This retrospective observational study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…This is likely attributable to the small number of patients with leakage. In line with our results, the efficacy of SLR in reducing bleeding was confirmed by several studies that concluded the benefit of SLR in this respect, whatever the method of reinforcement [ 25 , 30 , 35 , 38 41 ]. Close to our findings, Kwiatkowski et al [ 25 ], reported bleeding and leakage incidences of 4.6 and 2.3%, respectively, in the SLR group compared to 0% in the SLR group.…”
Section: Discussionsupporting
confidence: 91%
“…This is likely attributable to the small number of patients with leakage. In line with our results, the efficacy of SLR in reducing bleeding was confirmed by several studies that concluded the benefit of SLR in this respect, whatever the method of reinforcement [ 25 , 30 , 35 , 38 41 ]. Close to our findings, Kwiatkowski et al [ 25 ], reported bleeding and leakage incidences of 4.6 and 2.3%, respectively, in the SLR group compared to 0% in the SLR group.…”
Section: Discussionsupporting
confidence: 91%